Complexity of phenotypes induced by p.Asn1303Lys-CFTR correlates with difficulty to rescue and activate this protein - Farhat, Raí«d; El-Seedy, Ayman; Norez, Caroline; Talbot, Hugo; Pasquet, Marie-Claude; Adolphe, Catherine; Kitzis, Alain; Ladevèze, Véronique (Cellular and Molecular Biology, 2017)
Cystic Fibrosis is the most common recessive autosomal rare disease found in Caucasian. It is caused by mutations on the Cystic Fibrosis Transmembrane Conductance Regulator gene (CFTR) that encodes for a protein located on the apical membrane of epithelial cells. c.3909C>G (p.Asn1303Lys) is one of the most common worldwide mutations located in nucleotide binding domain 2. The effect of the p.Asn1303Lys mutation on misprocessing was studied by immunofluorescence and western blotting analysis in presence and absence of treatment. To evaluate the functionality of potentially rescued p.Asn1303Lys-CFTR, we assessed the channel activity by radioactive iodide efflux. No recovery of the activity was observed in transfected cultured cells treated with VX-809. Thus, our results suggest that multiple drugs may be needed for the treatment of c.3909C>G patients in order to correct and activate p.Asn1303Lys-CFTR as it shows folding and functional defects.